Peran dinas komunikasi dan informatika dalam mewujudkan informasi yang beretika dan bertanggung jawab di Kabupaten Sampang - Eko Haryansyah, Septian; Anas, Zulviar (Nur Science Institute, 2021)
The high level of violations in the use of social media and the lack of public knowledge about ethical and responsible information creates several problems in information and communication. In this case, the communication and informatics department of Sampang Regency plays a role in creating ethical and responsible information. Based on this, the researcher wants to research the role of the communication and informatics department in creating ethical and responsible information in the Sampang Regency. This study aims to determine the role of the communication and informatics office in creating ethical and responsible information and the factors that influence the role of the communication and informatics office in creating ethical and responsible information in the Sampang Regency. This study uses the concept of role theory, which explains several indicators such as informants, facilitators, and mediators. Based on the research, it can be seen that the role of the communication and informatics department in creating ethical and responsible information in Sampang Regency is still not maximized. Furthermore, the influencing factors are communication, resources, facilities, funds, and budget.